Mental health epidemiology today: a monitor of distress - Cooper, Brian (Epidemiology and psychiatric sciences, 2012)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS2045796012000066/resource/name/firstPage-S2045796012000066a.jpg